Aluminosilicates - Urozov Sharofiddin Mamarasulovich (Western European Studies, 2024)
Just as lead isotopes accumulate due to the decay of uranium contained in minerals that make up rocks and ores, radiogenic argon also accumulates in the mineral as a result of the decay of the potassium-40 isotope. Tests and experiments show that radiogenic argon is relatively well preserved in mica. For this reason, the potassium-argon method is widely used to determine the absolute age of mica.
Keywords: Feldspar; mica; potassium; sodium